2020
DOI: 10.1007/s40618-020-01381-8
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment is associated with reduced adipose tissue dysfunction and nonalcoholic fatty liver disease in obese hypogonadal men

Abstract: Purpose In both preclinical and clinical settings, testosterone treatment (TTh) of hypogonadism has shown beneficial effects on insulin sensitivity and visceral and liver fat accumulation. This prospective, observational study was aimed at assessing the change in markers of fat and liver functioning in obese men scheduled for bariatric surgery. Methods Hypogonadal patients with consistent symptoms (n = 15) undergoing 27.63 ± 3.64 weeks of TTh were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 112 publications
1
18
0
Order By: Relevance
“…Some studies have shown that men with simple steatosis or advanced NAFLD had lower testosterone levels than healthy controls of the same age [ 12 , 54 ]. Moreover, a recent study found that testosterone treatment is associated with reduced adipose tissue dysfunction and NAFLD in obese hypogonadal men, which suggests that testosterone may play a protective role in the progression of NAFLD and improves NAFLD by reducing intrahepatic triglycerides content [ 55 ]. While testosterone formulations are approved for men, they are not recommended for women [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that men with simple steatosis or advanced NAFLD had lower testosterone levels than healthy controls of the same age [ 12 , 54 ]. Moreover, a recent study found that testosterone treatment is associated with reduced adipose tissue dysfunction and NAFLD in obese hypogonadal men, which suggests that testosterone may play a protective role in the progression of NAFLD and improves NAFLD by reducing intrahepatic triglycerides content [ 55 ]. While testosterone formulations are approved for men, they are not recommended for women [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male patients with hypogonadism and NAFLD could possibly benefit from testosterone administration [150,151]. However, the longterm safety profile of this therapy, including cardiovascular outcomes, remains unclear.…”
Section: Thyroid Disease and Thyromimeticsmentioning
confidence: 99%
“…[110][111][112][113] While these data provide evidence for a role of testosterone in the inhibition of adipogenesis in pre-adipocytes, they do not explain the action of testosterone to reduce the mass of preexisting fat depots in humans and rodents. Other mechanisms by which testosterone may regulate fat mass include modulation of lipid metabolism, 114,115 alteration of muscle metabolism 116 and alteration of mitochondrial function 117 ; with these actions being extensively reviewed elsewhere 118 therapies exhibited an increase in whole body fat mass of 11.2% for leuprolide and 6.4% for bicalutamide. 119 Similar increases in fat mass following bicalutamide 120 and enzalutamide 121,122 monotherapy have also been reported supporting a role for testosterone acting via the AR to regulate fat mass.…”
Section: Preclinical Orchidectomy Models To Investigate Testosterone ...mentioning
confidence: 99%